O22 The effects of fibular repositioning taping on joint stiffness and joint angle of the lower extremity during a drop landing. (17th September 2017) - Baker, R; Jun, H; Chun, YM; Kim, JA; Lee, SY
Abstract : Study Design: Control study. Objectives: To investigate effects of Fibular Repositioning Taping (FRT) on lower extremity joint stiffness and angle during drop-landing. Background: Various taping strategies have been used to prevent ankle sprains. The FRT requires less material and skill than traditional taping. Currently, little is known regarding how FRT effects lower extremity biomechanics. Methods and Measures: Twenty-eight participants (14 healthy, 14 with chronic ankle instability [CAI]) performed drop-landings from a 60 cm box; three were performed prior to tape application and three were performed post-FRT. Three-dimensional kinematic and kinetic data were collected using an infrared optical camera system (Vicon Motion Systems Ltd. Oxford, UK) and force-plate (AMTI, Watertown, MA). Joint stiffness and sagittal angle of the ankle, knee, and hip were analysed. Results: The hip [Healthy: p<0.05; M±SD: 29.43±11.27(pre), 33.04±12.03(post); CAI: p<0.05; M±SD: 31.45±9.70(pre), 32.29±9.85(post)] and knee [Healthy: p<0.05; M±SD: 53.44±8.09(pre), 55.13±8.36(post); CAI: p<0.05; M±SD: 53.12±8.35(pre), 55.55±9.81(post)] joints demonstrated significant increases in sagittal angle after FRT. A significant decrease in joint angle was found at the ankle [Healthy: p<0.05; M±SD: 56.10±3.71(pre), 54.09±4.31(post); CAI: p<0.05; M±SD: 52.80±6.04(pre), 49.86±10.08(post)]. A significant decrease in hip [Healthy: p<0.05; M±SD: 1549.16±517.53(pre), 1272.48±646.73(post); CAI: p<0.05; M±SD: 1300.42±595.55(pre), 1158.27±550.58(post)] and knee [Healthy: p<0.05; M±SD: 270.12±54.07(pre), 239.13±64.70(post); CAI: p<0.05; M±SD: 241.58±93.48(pre), 214.63±101.00(post)] joint stiffness was found post-FRT application, while no difference was found at the ankle [Healthy: p>0.05; M±SD: 57.29±17.04(pre), 59.37±18.30(post); CAI: p>0.05; M±SD: 69.15±17.63(pre), 77.24±35.05(post)]. Conclusion: FRT application decreased joint angle at the ankle without altering ankle joint stiffness. In contrast, decreased joint stiffness and increased joint angle was found at the hip and knee following FRT. Thus, participants utilise an altered shock absorption mechanism during drop-landings following FRT. When compared to previous research, the joint kinematics and stiffness of the lower extremity appear to be different following FRT versus traditional ankle taping.